The Role of the Board of Directors in the Bankruptcy Process of Individual Companies: Analysis of Positivism with an Artificial Intelligence Approach - Wahyu Widodo; Zainal Arifin Hoesein (Publikasi Indonesia, 2024)
The Job Creation Law and Government Regulation No. 8 of 2021 introduces an individual company owned by one individual. This can confuse personal and corporate interests and obscure responsibilities between directors and shareholders and is vulnerable the risk of bankruptcy. Analyzing the role of directors in the bankruptcy process through legal positivism is important to understand legal responsibilities and protections. Additionally, advances in artificial intelligence (AI) can improve decision-making efficiency and accuracy. The purpose of this study is to identify and analyze the role of directors in the bankruptcy process individual companies through the lens of positivism, as well as to explore the integration of artificial intelligence in improving board decision-making. The research method used is normative juridical, using a legislative approach and an analytical approach. The results of the study show that the board of directors has an important role in managing the bankruptcy process, especially in data-driven decision-making. In the event of bankruptcy, the board of directors faces certain legal consequences in accordance with Articles 16, 69 paragraphs (1), 97, and 104 of Law No. 37 of 2004 concerning Bankruptcy, as well as Article 93 of Law No. 40 of 2007 concerning Limited Liability Companies. Artificial intelligence has been proven help directors in analyzing risks and predicting outcomes, making decisions more informative and strategic. This study concludes that the application of positivism and artificial intelligence in the analysis of the role of directors in the bankruptcy process improves the effectiveness and efficiency of decision-making, especially in complex situations.